In silico studies to understand the interactions of flavonoid inhibitor with nsp12-RNA dependent RNA polymerase of SARS-CoV-2 and its homologs - Shamiya Anwar Kizhakkiniyakath; Tejaswini Choudhury; Madhan Vishal Rajan; Sagar Rathee; Basant Meena; Gururao Hariprasad (Biochemistry and Biophysics Reports)
Aim: COVID 19 continues to be a major health concern. RNA dependent RNA polymerase of SARS-CoV-2 which is crucial for replication is therefore a potential drug target. Methodology: Based on experimental structures of RdRp from SARS-CoV-2, computational models were generated of its homologs from SARS-CoV-1, MERS and Bat. SARS CoV-2 RdRp was used for virtual screening at nucleotide binding site with molecule from COCONUT Natural Products database using Glide. Complexes with the top inhibitor molecule were modelled using Discovery Studio and Desmond suite of programs. Results: SARS-CoV-2 RdRp has a minimum of 80 % sequence similarity with its homologs, with the secondary structural elements, catalytic residues and metal binding residues being conserved. Certain residue variations in SARS-CoV-2 RdRp seems to be responsible for the stability of the enzyme. Docking and simulation studies showed that a flavonoid molecule with Coconut ID: CNP0127177.0 (HHF318) has binding affinity in low nano-molar range against RdRp from SARS-CoV-2 which was comparable or better than currently used inhibitors. This affinity stems from cationic-π with Arg555, and π-stacking interactions with a nucleobase of RNA. Molecule also engages with other residues that are crucial for its functions. This flavonoid molecule has similar physio-chemical properties like ATP towards SARS-CoV-2 RdRp, and has low potency for human ATP binding proteins. Conclusion: HHF318 is a potential inhibitor of SARS-CoV-2 RdRp with good potency, specificity and pharmacokinetic properties for it to be developed as a drug candidate for COVID19.